Peerless and Periled : the Paradox of American Leadership in The World Economic Order. - Suominen, Kati (Stanford University Press, 2012)
As the world economy emerges from the financial crisis, critics are announcing an end of the American era. The United States is said to be in an inexorable decline, and the expectation for the 21st century is for China to eclipse America and for the contours of global governance to blur. The loss of America's preeminent status will undercut our sway abroad and our safety and standard of living at home. But is America really done? Is the American era really over? In this provocative account, based on interviews with senior policymakers and cutting-edge research, Kati Suominen argues that talk.